2022
DOI: 10.3390/agriculture12101539
|View full text |Cite
|
Sign up to set email alerts
|

Application of Desert DSEs to Nonhost Plants: Potential to Promote Growth and Alleviate Drought Stress of Wheat Seedlings

Abstract: To evaluate the applicability of desert dark septate endophytes (DSEs) in crop cultivation, Alternaria alternata (Fr.) Keissl. (Aa), Paraphoma pye Moslemi & P.W.J. Taylor (Pp), and Paraphoma radicina (McAlpine) Morgan-Jones & J.F. White (Pr) were inoculated into nonhost wheat growing under three water conditions. The plants’ biomass, vegetative growth, and physiological parameters were investigated. At harvest, all DSE strains were effective colonizers under all treatments. These DSEs generally positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…Plant tissue harbors a wide diversity of root endophytic fungi which are mainly beneficial symbionts, comprising DSEs [122]. These DSEs inhabit plant root tissues in different ecosystems, particularly in extreme desert ecosystems; they often form symbiotic associations with the epidermis and the cortex of plant roots in arid and semi-arid environments [106,[123][124][125][126]. These sterile ascomycetous DSEs are categorized by melanized dark septate hyphae with microsclerotia that colonize the roots of numerous plant species, both intracellularly and extracellularly [127][128][129].…”
Section: Dark Septate Endophytes (Dses) and Drought Stress Tolerance ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Plant tissue harbors a wide diversity of root endophytic fungi which are mainly beneficial symbionts, comprising DSEs [122]. These DSEs inhabit plant root tissues in different ecosystems, particularly in extreme desert ecosystems; they often form symbiotic associations with the epidermis and the cortex of plant roots in arid and semi-arid environments [106,[123][124][125][126]. These sterile ascomycetous DSEs are categorized by melanized dark septate hyphae with microsclerotia that colonize the roots of numerous plant species, both intracellularly and extracellularly [127][128][129].…”
Section: Dark Septate Endophytes (Dses) and Drought Stress Tolerance ...mentioning
confidence: 99%
“…Several reports indicate that DSEs are extensively found in plants in arid and semiarid environments and can improve the tolerance of host plants to drought stress [106,126,[144][145][146]. It is suggested that DSE fungi in water-limited environments normally show positive responses to host plants in terms of drought tolerance and resistance [106,126]. The mechanism is perhaps related to significantly increased superoxide dismutase (SOD) activity under drought stress to remove ROS and cope with oxidative damage.…”
Section: Dark Septate Endophytes (Dses) and Drought Stress Tolerance ...mentioning
confidence: 99%
“…These beneficial effects could result from an increase in the expression of key genes as well as hormonal and metabolic pathways, including an increase in stress tolerance-related osmolytes (e.g., proline and starch), ecophysiological performance, and protection of membranes, among others ( Azad and Kaminskyj, 2016 ; Dastogeer, 2018 ; Acuña-Rodríguez et al., 2019 ; Molina-Montenegro et al., 2020 ). In fact, several studies have demonstrated that inoculation with endophytes from extreme environments such as Antarctica or Deserts can improve the antioxidant system in native plants as well as in crops to cope with the abiotic stress prevailing in this harsh ecosystems ( Ramos et al., 2018 ; Hereme et al., 2020 ; Li et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi, which are distributed in plants within a wide range of habitats, are a group of microorganisms that exist inside healthy plant tissues without causing obvious disease symptoms to the host plants [1][2][3]. Endophytic fungi are capable of promoting plant growth, modulating plant development, and protecting host plants from a wide variety of biotic and abiotic stresses [4,5]. Some studies reported that the composition and distribution of endophytic fungal communities vary with plant species and ecological environment [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%